Saken Seifullin — the organizer of national education in Kazakhstan - Kassimova, S.S. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the article a comprehensive analysis of S. Seifullin's public educational activities, which contributed to the development of national education in Kazakhstan is presented. On the basis of new data of archival funds, the state of education of S. Seifullin during the rule of the Government of Kazakhstan in 1922–1924 was relatively widespread. In April 1924, the regional organization «Eradicate Illiteracy» was organized. The republican newspaper «Sovetskaya step» has published the message to the society «Literate, teach one illiterate!». The Society has been very active in all the provinces and counties of Kazakhstan and has done a great job in educating adults and children of school age. The authors classify the academic achievements of this period as follows: at first, the number of Kazakh schools has increased, and the communal schools adapted to the life of the Kazakhs have justified themselves, and the elimination of illiteracy is growing; secondly, a new breakthrough was made to improve the material conditions of schools; thirdly, textbooks for Kazakh schools were published; physics and hygiene textbooks were first published in the Kazakh language; fourthly, a vocational education system has been established as the basis of educational institutions that train teachers; fifthly, in the years of higher education, S. Seifullin made a great contribution to the training of teachers. Graduates of the educational institutions have been promoted to prominent scientists and statesmen of the republic, contributing to the development of culture and science, education in the country. In addition, the authors analyzed education articles published by S. Seifullin in the pages of newspapers, where the results of the realization of the ideas proved by the work of the Kazakh government.
Сəкен Сейфуллин — Қазақстандағы халық ағарту ісінің ұйымдастырушысы
Сакен Сейфуллин — организатор народного просвещения в Казахстане
Keywords: education; «Eradicate Illiteracy»; Government; commune schools; National Commissariat for Education